Are health care professionals advising obese patients to lose weight? - Galuska, D A; Will, J C; Serdula, M K; Ford, E S (JAMA : the journal of the American Medical Association, 1999)
Implementation of the National Institutes of Health's 1998 guidelines, which recommended that health care professionals advise obese patients to lose weight, required baseline data for evaluation. To describe the proportion and characteristics of obese persons advised to lose weight by their health care professional during the previous 12 months and to determine whether the advice was associated with reported attempts to lose weight. The Behavioral Risk Factor Surveillance System, a random-digit telephone survey conducted in 1996 by state health departments. Population-based sample from 50 states and the District of Columbia. A total of 12835 adults, 18 years and older, classified as obese (body mass index > or =30 kg/m2), who had visited their physician for a routine checkup during the previous 12 months. Reported advice from a health care professional to lose weight, and reported attempts to lose weight. Forty-two percent of participants reported that their health care professional advised them to lose weight. Using multivariate logistic regression analysis, we found that the persons who were more likely to receive advice were female, middle aged, had higher levels of education, lived in the northeast, reported poorer perceived health, were more obese, and had diabetes mellitus. Persons who reported receiving advice to lose weight were significantly more likely to report trying to lose weight than those who did not (OR, 2.79; 95% CI, 2.53-3.08). Less than half of obese adults report being advised to lose weight by health care professionals. Barriers to counseling need to be identified and addressed.